Multi-spectroscopic monitoring of molecular interactions between an amino acid-functionalized ionic liquid and potential anti-Alzheimer's drugs. Issue 64 (23rd October 2020) - Sharma, Srishti; Banjare, Manoj Kumar; Singh, Namrata; Korábečný, Jan; Kuča, Kamil; Ghosh, Kallol K.
Abstract : Ionic liquids mediated interactions are an expedient approach that exhibit inhibition effect on amyloid fibrils which is beneficial for the treatment of Alzheimer's disease. Abstract : Inhibiting the formation of amyloid fibrils is a crucial step in the prevention of the human neurological disorder, Alzheimer's disease (AD). Ionic liquid (IL) mediated interactions are an expedient approach that exhibits inhibition effects on amyloid fibrils. In view of the beneficial role of ILs, in this work we have explored complexation of anti-Alzheimer's drugs ( i.e., tacrine and PC-37) and an amino acid-functionalized IL [AIL (4-PyC8)]. Maintaining standard physiological conditions, the binding mechanism, thermo-dynamical properties and binding parameters were studied by employing UV-vis, fluorescence, FTIR, 1 H NMR, COSY and NOESY spectroscopy. The present investigation uncovers the fact that the interaction of anti-Alzheimer's drugs with 4-PyC8 is mediated through H-bonding and van der Waals forces. The Benesi–Hildebrand relation was used to evaluate the binding affinity and PC-37 showed the highest binding when complexed with 4-PyC8. FTIR spectra showed absorption bands at 3527.98 cm −1 and 3527.09 cm −1 for the PC-37 + 4-PyC8 system which is quite promising compared to tacrine. 1 H-NMR experiments recorded deshielding for tacrine at relatively higher concentrations than PC-37. COSY investigations suggest that anti-Alzheimer's drugs after complexation with 4-PyC8 show a 1 : 1 ratio. The cross-peaks of the NOESY spectra involve correlations between anti-Alzheimer's drugs and AIL protons, indicating complexation between them. The observed results indicate that these complexes are expected to have a possible therapeutic role in reducing/inhibiting amyloid fibrils when incorporated into drug formulations.